ANALISA KEKUATAN FLANGE PADA SISTEM PEMIPAAN PRIMER REAKTOR TRIGA 2000 BANDUNG - Hendra Prihatnadi; Budi Santoso (Jurnal Perangkat Nuklir, 2011)
In the primary cooling system installation TRIGA 2000 reactor, grafting piping system using flange connection for connecting or demolition if necessary. This connection includes a connection pipe to the fittings, valves, equipment, or other separate parts in the piping system. Analysis of flange force on the primary coolant piping system of the TRIGA 2000 reactor was performed with stress analysis software CAESAR II. The steps required in the analysis include data collection for model input, modeling, static analysis. Analysis of flange strength using the "Flange as the weakest part philosophy" with full term rating that is used when pressure-temperature values ​​specified in ASME B16.5 is taken as Maximum allowable working pressure (MAWP) in the primary reactor coolant system piping TRIGA 2000. Analysis of flange force that removed in the 2000 Bandung TRIGA reactor at the primary discharge piping system. From the calculation results obtained that the flange is eligible in accordance with the MAWP for the temperature and operating pressure of the TRIGA 2000 reactor primary system. Dalam instalasi sistem pendingin primer reaktor TRIGA 2000, sistem penyambungan pemipaannya menggunakan sambungan flange untuk menghubungkan atau pembongkaran apabila diperlukan. Sambungan ini meliputi sambungan pipa ke fitting, katup, equipment, atau bagian lainnya yang terpisah dalam sistem pemipaan. Analisis kekuatan flange pada sistem pemipaan pendingin primer reaktor TRIGA 2000 dilakukan dengan bantuan perangkat lunak analisa stress CAESAR II. Langkah-langkah yang dibutuhkan dalam analisis meliputi pengumpulan data untuk input model, pemodelan, analisis statik. Analisis kekuatan flange menggunakan metode “Flange as weakest part philosophy” dengan istilah full rating yang dipakai bila nilai pressure-temperature tertentu pada ASME B16.5 diambil sebagai Tekanan Kerja Maksimum yang diijinkan atau Maximum Allowable Working Pressure (MAWP) pada sistem perpipaan pendingin primer reaktor TRIGA 2000. Analisa kekuatan flange yang dilalukan di reaktor TRIGA 2000 Bandung yaitu pada bagian discharge sistem pemipaan primer. Dari hasil perhitungan diperoleh bahwa flange memenuhi syarat sesuai dengan MAWP untuk suhu dan tekanan operasi sistem primer reaktor TRIGA 2000.